Progress in Synthesis and Photocatalytic Activity of MAl2O4(M=Mg, Sr, Ba) Based Photocatalysts - Han, Xiulin; Sun, Meijuan; Chai, Xiaona; Li, Jun; Wu, Yanning; Sun, Wu (Frontiers in Materials, 2022)
Photocatalysis is regarded as a green technology to degrade organic dyes driven by light energy. The selection of photocatalyst restricts the development of photocatalytic technology. Aluminate is a kind of potential broad-gap semiconductor photocatalyst and also an excellent phosphor substrate materials. The physical and chemical properties of aluminate are strongly dependent on the preparation method. Insight into the influence of synthesis methods on photocatalytic activity of aluminate based photocatalysts is helpful for the development of novel aluminate based photocatalysts. In this paper, the typical synthesis methods of aluminate photocatalysts, ion-doped aluminate based photocatalysts and heterojunction type aluminate photocatalysts, and their photocatalytic activities are reviewed. Based on the energy band theory, the photocatalytic mechanisms of single component aluminate photocatalyst, ion-doped aluminate based photocatalyst, and heterojunction type aluminate photocatalyst were reviewed. The future development of aluminate based photocatalyst will give priority to the salinization of aluminate modified by silver and other metal particles and the photocatalytic application of activated ion modified aluminate based phosphors.